2000
DOI: 10.1302/0301-620x.82b3.9834
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the position of the limb on venous impulse foot pumps

Abstract: Compression foot pumps are widely used for the prevention of postoperative venous thrombosis. We tested the efficiency of the pump in ten healthy subjects; the velocity of venous blood flow in the common femoral vein was measured in the horizontal, Trendelenberg (foot-up) and reverse-Trendelenberg (foot-down) positions. Application of the foot pump produced an increase in the venous velocity in all subjects. The mean increase in the horizontal position was 27.2% and in the Trendelenberg position 15.4%. In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…Results from four independent randomised clinical trials have shown that mechanical prophylaxis with foot pumps in THR achieved equivalent -if not superior -results compared to chemical management [5,11,13,16], but the tolerance of the device has been a problem for some patients [3,12]. The effective action of the foot pumps depends on various factors, including the frequency and pressure of the impulses and the dependency of the lower extremities [1,4,10]. It is not known whether the efficacy, safety and compliance of the foot pumps are enhanced by the simultaneous use of graduated compression stockings (GCS).…”
Section: Introductionmentioning
confidence: 99%
“…Results from four independent randomised clinical trials have shown that mechanical prophylaxis with foot pumps in THR achieved equivalent -if not superior -results compared to chemical management [5,11,13,16], but the tolerance of the device has been a problem for some patients [3,12]. The effective action of the foot pumps depends on various factors, including the frequency and pressure of the impulses and the dependency of the lower extremities [1,4,10]. It is not known whether the efficacy, safety and compliance of the foot pumps are enhanced by the simultaneous use of graduated compression stockings (GCS).…”
Section: Introductionmentioning
confidence: 99%
“…We recommend that the device be set at 30-second intervals to allow for maximum pooling of venous blood in the plantar plexus. The more volume of blood in the chamber may allow for the foot pump to facilitate greater augmentation of blood with primary compression [10]. Patient characteristics that might effect venous velocity augmentation with mechanical devices have been unexplored.…”
Section: Discussionmentioning
confidence: 99%
“…During the examinations, we placed the subjects in a 308-reverse Trendelenburg position with the leg externally rotated to minimize active dorsal or plantar flexion. The literature suggests that the use of venous impulse foot pumps while subjects are in a reverse Trendelenburg position may increase the thromboprophylactic effect [10].…”
Section: Methodsmentioning
confidence: 99%
“…Compression foot pumps are widely used to increase perfusion and reduce the risk of post operative venous thrombosis, but are generally used for postoperative patients who are confined to bed for prolonged periods of time (Fleming et al, 2000). Until recently …”
Section: Introductionmentioning
confidence: 99%